Management of Vesicoureteral Reflux: What Have We Learned Over the Last 20 Years? - Läckgren, Göran; Cooper, Christopher S.; Neveus, Tryggve; Kirsch, Andrew J. (Frontiers in Pediatrics, 2021)
Vesicoureteral reflux (VUR) is associated with increased risks of urinary tract infection, renal scarring and reflux nephropathy. We review advancements over the last two decades in our understanding and management of VUR. Over time, the condition may resolve spontaneously but it can persist for many years and bladder/bowel dysfunction is often involved. Some factors that increase the likelihood of persistence (e.g. high grade) also increase the risk of renal scarring. Voiding cystourethrography (VCUG) is generally considered the definitive method for diagnosing VUR, and helpful in determining the need for treatment. However, this procedure causes distress and radiation exposure. Therefore, strategies to reduce clinicians’ reliance upon VCUG (e.g. after a VUR treatment procedure) have been developed. There are several options for managing patients with VUR. Observation is suitable only for patients at low risk of renal injury. Antibiotic prophylaxis can reduce the incidence of UTIs, but drawbacks such as antibiotic resistance and incomplete adherence mean that this option is not viable for long-term use. Long-term studies of endoscopic injection have helped us understand factors influencing use and the effectiveness of this procedure. Ureteral reimplantation is still performed commonly, and robot-assisted laparoscopic methods are gaining popularity. Over the last 20 years, there has been a shift towards more conservative management of VUR with an individualized, risk-based approach. For continued treatment improvement, better identification of children at risk of renal scarring, robust evidence regarding the available interventions, and an improved VUR grading system are needed.